THE IMPORTANCE OF COMMUNICATION LITERACY IN THE DIGITAL WORLD: PREPARING THE PUBLIC TO FACE TECHNOLOGICAL CHALLENGES IN INDONESIA - Furbani, Widiastuti (PT. Hafasy Dwi Nawasena, 2025)
The rapid expansion of digital communication technologies has reshaped how individuals access, interpret, and engage with information in everyday life. In Indonesia, communication literacy emerges as a core competency for navigating algorithm-driven, user-generated, and AI-mediated environments. This study conducts a Systematic Literature Review (SLR) of 43 peer-reviewed and reputable sources (2019–2024) to synthesize conceptual and empirical evidence on the cultural, cognitive, emotional, and ethical dimensions of digital communication literacy. Searches (Scopus, Web of Science, SINTA, Google Scholar) and thematic coding reveal uneven literacy across the population, shaped by generational disparities, educational gaps, platform logics, and socio-cultural norms. Findings also highlight heightened risks introduced by AIrequiring competencies that extend beyond technical skills to include multimodal interpretation, metacognitive reflection, and algorithmic awareness. The review formulates a holistic framework integrating critical thinking, multimodal reading/production, ethical reasoning, and socio-emotional capacities, and translates it into practice areas for education, civic participation, and the digital economy. Strengthening communication literacy in Indonesia is therefore essential not only for healthier democratic discourse and social cohesion, but also for sustained competitiveness in a datafied, AI-intensive economy.